2005
DOI: 10.1111/j.1478-3231.2005.01076.x
|View full text |Cite
|
Sign up to set email alerts
|

SEN virus infection influences the pathological findings in liver but does not affect the incidence of hepatocellular carcinoma in patients with chronic hepatitis C and liver cirrhosis

Abstract: SEN-V co-infection may influence the histopathological features of the livers of patients with type C CH and LC but does not affect the outcome of patients with type C chronic liver disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…In addition, M.M. has been reported in a number of journals on the relationship between the degree of IR of hepatocytes and the pathogenesis of HCC development 3,13,[21][22][23][24][25][26][27][28] The sections were mounted on a laser-capture microscope (LMD6500 system, Leica Microsystems), and LCM was performed within 72 h of the staining. The micro-dissected sections were collected in tube caps (Thermo Scientific Japan, Yokohama, Japan) with 10 μL of solution no.…”
Section: Histological Evaluationmentioning
confidence: 99%
“…In addition, M.M. has been reported in a number of journals on the relationship between the degree of IR of hepatocytes and the pathogenesis of HCC development 3,13,[21][22][23][24][25][26][27][28] The sections were mounted on a laser-capture microscope (LMD6500 system, Leica Microsystems), and LCM was performed within 72 h of the staining. The micro-dissected sections were collected in tube caps (Thermo Scientific Japan, Yokohama, Japan) with 10 μL of solution no.…”
Section: Histological Evaluationmentioning
confidence: 99%
“…Although SEN virus is found in the serum of a large percentage (13–67%) of patients with HCC, no study has shown the incidence of the tumour in these patients to be significantly higher than that in the corresponding control groups . For example, a study in Thailand that included a control group and patients chronically infected with HCV or HBV showed that SEN virus infection alone was not associated with HCC development .…”
Section: Sen Virusmentioning
confidence: 99%
“…In addition, Yoshida et al (2002) reported no significant differences between SENVpositive and SENV negative patients regarding serum albumin, total bilirubin and transaminase levels. Also, many studies reported absence of significant difference in the blood biochemical parameters between the SENV DNA-positive and -negative chronic hepatitis patients (Tangkijvanich et al, 2003;Moriyama et al, 2005).…”
mentioning
confidence: 99%
“…On the contrary, another study documented that SENV co-infection may influence the histopathological features of the livers of patients with CHC but does not affect the outcome of patients with type C chronic liver disease. The histological features of the livers of SENV DNA-positive patients included more severe parenchymal inflammatory cell infiltration and more immune response (Moriyama et al, 2005).…”
mentioning
confidence: 99%